Pentingnya pembelajaran kontekstual (contextual teaching learning) dalam pembelahjaran di sekolah dasar - Aghfar, M.Sambuaga (Maliki Interdisciplinary Journal, 2025)
Contextual Teaching and Learning (CTL) approaches are increasingly popular in elementary education because they are effective in connecting subject matter to students’ real lives. This article analyzes the core concepts in CTL, such as constructivism, inquiry, reflection, and authentic assessment, and outlines their benefits in elementary school learning. Through conceptual analysis methods, this study shows that contextual learning not only helps students understand the material more deeply, but also encourages the development of critical, creative, and collaborative thinking skills. This article emphasizes the important role of teachers as facilitators in creating authentic and life-relevant learning environments for students. As a result, CTL has been shown to increase students’ learning motivation and make learning more meaningful, as well as support the achievement of the Pancasila student profile.